Competition between Inter and Intramolecular Tetrel Bonds: Theoretical Studies Complemented by CSD Survey. Issue 10 (19th April 2021) - Zierkiewicz, Wiktor; Grabarz, Anna; Michalczyk, Mariusz; Scheiner, Steve
Abstract: Crystal structures document the ability of a TF3 group (T=Si, Ge, Sn, Pb) situated on a naphthalene system to engage in an intramolecular tetrel bond (TB) with an amino group on the adjoining ring. Ab initio calculations evaluate the strength of this bond and evaluate whether it can influence the ability of the T atom to engage in a second, intermolecular TB with another nucleophile. A very strong CN − anionic base can approach the T either along the extension of a T−C or T−F bond and form a strong TB with an interaction energy approaching 100 kcal/mol, although this bond is weakened a bit by the presence of the internal T⋅⋅⋅N bond. The much less potent NCH base engages in a correspondingly longer and weaker TB, less than 10 kcal/mol. Such an intermolecular TB is weakened by the presence of the internal TB, to the point that it only occurs for the two heavier tetrel atoms Sn and Pb. Abstract : Competing tetrel bonds : TF3 (T=Si, Ge, Sn, Pb) situated on a naphthalene skeleton is able to engage not only in an intramolecular tetrel bond (TB) with amino group but also in an intermolecular bond with Lewis base as well.